Effects of Sugar Cane Filter Cake Compost on Selected Characteristics of BRIS Soils and Growth of Maize - Mohamed Omar, Yossif Salama (2009)

(untitled)
Beach Ridges Interspersed with Swales (BRIS) soil usually poses a great challenge for water and nutrients management due to the relatively low water holding and nutrient retention capacities. Besides, high hydraulic conductivity, such soils can also contribute to high leaching. Addition of organic wastes to BRIS soil has beneficial effects upon soil structure and properties related to it. Incubation study and field lysimeter experiments were conducted to investigate the effect of sugar cane filter cake compost on selected physical, chemical and biological properties of BRIS soil and its effect on growth and yield of maize. In both incubation and field experiments, the BRIS soil was amended with 0, 3, 6, 8, 12 tonnes ha-1 of filter cake compost, arranged in completely randomized and lattice square designs, respectively.The amounts of OC, N, P, K, Ca and Mg in filter cake compost were 13.60%, 1.10%, 1.00%, 0.20%, 7.00%, 0.80%, respectively. The incubation study showed that the release of different nutrients varied according to treatments and the mean range of nutrients released at the end of incubation period were; 0.012-0.035 % N, 0.42-0.55 % OC, 33.80-60.20 ppm NO- 3, 20.40-66.97 ppm NH4 + , 0.06-3.19 cmol kg-1 Ca and 0.03- 0.08 cmol kg-1 Mg. Addition of 12 ton ha-1 of the filter cake compost significantly increased the total N and NH4 +contents of the soil compared with unamended control. The soil OC content responded as y = 0.42+0.01x (P = 0.036, R2 = 0.96). The soil OC showed linear increase with increasing rates of filter cake compost. Field study conducted for two consecutive seasons showed that the addition of the filter cake compost yielded no significant impact on the soil pH for the first season, but in the second season a significantly higher soil pH was obtained with addition of 12 t ha-1 of filter cake compost compared to the control and 3 t ha-1 treatments. Soil pH responded as quadratic relationship where y = 7.13 + 0.19x - 0.008x2 (P = 0.0144, R2=0.99). The available soil water responded as y = 2.08 - 0.17x + 0.03x2 (P = 0.00436, R2 = 0.96) in the first season and y = 2.5+ 0.12x (P = 0.0254, R2 = 0.85) in the second season. In the first season, soil N responded as linear relationship, where y = 0.022 +0.004x (P=0.0449, R2=0.78) up to 12 t ha-1, while in the second season, it responded as linear relationship, where y = 0.04 + 0.0003x (P=0.0452, R2=0.78) with the increment rate of filter cake compost up to 12 t ha-1. The soil Ca responded as y = 0.013 + 0.03x – 0.001x2 (P = 0.0148, R2 = 0.98) and y = 0.04 x – 0.002x2 (P = 0.0009, R2 = 0.99) during first and second season, respectively. Maximum Ca content was attained at 0.13 cmol kg-1 in the first season and 0.21 cmol kg-1 for season two due to filter cake compost rates at 10.50 and 10 t ha-1, respectively. There was no significant increase in microbial activity due to low fresh carbon sources in the compost. Although applying filter cake compost increases the physical and chemical condition of BRIS soil, further investigation on the economic implication of such organic amendment should be conducted. Keywords: Sugar canes filter cake compost, sandy soils, soil amendment, and plant growth.